Plasmacytoid dendritic cells control B cell-derived IL-10 production - Georg, Philipp; Bekeredjian-Ding, Isabelle (Autoimmunity, 2012)
Plasmacytoid dendritic cells (pDC) exert contradictory roles: they represent major players in the pathogenesis of type I interferon-mediated autoimmunity but contribute to tolerance in the transplant setting. In this study we describe pDC as cellular enhancers of B cell-derived IL-10 production, a mechanism recently described as relevant in maintaining peripheral tolerance. Our data demonstrate that in human peripheral blood pDC augment IL-10 production in B cells in response to TLR7 and -9 ligands. They further show that pDC themselves produce IL-10 in response to TLR stimulation, most prominently after triggering of TLR7. Additionally, the data indicate that the positive regulatory effect of pDC on IL-10 production is not due to type I interferon production or other soluble factors. We conclude that pDC/B cell contact is essential for B cell-mediated immune suppression.